Quality and evaluation as global educational political trends: comparative study of national evaluation agencies in compulsory education in Europe - Álvarez-López, Gabriel; Matarranz, María (Revista Complutense de Educación, 2020)
Assessment today is one of the main concerns of the developed conuntries. This concern lies on the need to improve the qual-ity of education systems and the sustainability of public policies. However, and despite the lack on consensus on how to face the chal-lenges posed by quality and evaluation in national education systems, the majority of developed states have assessment institutions and national evaluation programs. In this context, and taking into account the European reality, it is interesting to drax attention to whether these institutions and policies are sustainable at a supranational level and on what conditions these evaluations can be carried out. This paper intends to reflect on these issues by means of a study carried out on the assessment agencies of basic education in Germany, Italy and Spain. To carry out this research, we have followed the comparative methodology in education, since the objects of study present a degree of homogeneity – heterogeneity that allows us to consider them from this perspective. Through the analysis and previous reflection on quality as a current concern of contemporary educational systems, and evaluation as a global political trend, we draw conclusions that lead us to reflect on two questions: what do we mean by quality and how can evaluation contribute to its improvement? Can existing dominant models improve quality? From this reflection, we close the conclusions proposing the creation of a European Evaluation Agency for compulsory education, which will allow us to continue building a Common European area for research and innovation.